Pemanfaatan Pangan Lokal dalam Rangka Penerapan Gizi Seimbang: Use of Local Food in Order Implementation of Balanced Nutrition - Pellokila, Marthen Robinson; Chamdra, Santhy; Kareri, Indawati Rambu; Lena, Megawati Saputri A. R. Lay; Picauly, Intje (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Balanced nutritional intake is an important factor in supporting a person's health. When consuming food, you must pay attention to balanced nutritional intake. Therefore, in living a healthy lifestyle, everyone is encouraged to consume balanced nutritious food. The problem is, that not everyone understands the guidelines for balanced nutrition which must be implemented from the aspect of local food knowledge and processing. This community service activity aims to increase knowledge about the use of local food for implementing balanced food consumption and nutrition. This activity was carried out using counseling and training methods related to aspects of local food processing and education on the implementation of balanced nutrition with posyandu cadres, elderly cadres, and TP PKK women in Oefeto Village, Amabi Oefeto District, Kupang Regency in October 2024. The results obtained from this activity are changes in knowledge, attitudes, and actions in processing local food and implementing a balanced nutritional diet. It is recommended that this outreach activity continue to be encouraged to change community behavior regarding the use of local food to achieve balanced nutritional adequacy by local food.